Mentha rotundifolia (L.) Huds. aqueous extract attenuates H2O2 induced oxidative stress and neurotoxicity - Boualam, Khadija; Bouhaddou, Nezha; Sobeh, Mansour; Tabyaoui, Mohamed; Taghzouti, Khalid (Frontiers in Neuroscience, 2023)
Oxidative stress plays a causal role in neurodegenerative diseases. The aim of this study is to evaluate the antioxidant and neuroprotective effects of a widely used Moroccan plant, Mentha rotundifolia (L.) Huds (M. rotundifolia), in traditional medicine as well as a condiment. The chemical composition of M. rotundifolia aqueous extract was analyzed by liquid chromatography coupled to mass spectrometry (LC-MS). 2,2-diphenyl 1-picrylhydrazyle (DPPH) and 2,2'-azino-bis 3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assays were used to assess its in vitro antioxidant activity. H2O2 induced oxidative stress animal model was then used to confirm the protective effect of M. rotundifolia extract in vivo. Behavioral impairments were tested using Open Field, Y-maze and Rotarod tests to evaluate its neuroprotective effects. Hyperalgesia was assessed with tail immersion test. The LC-MS/MS analysis revealed a high content of kaempferol glucuronide (85%) in the extract. DPPH and ABTS IC50 values were 26.47 ± 1.68 and 41.21 ± 2.54 µg/ml, respectively. At the dose of 125 mg/kg, M. rotundifolia extract attenuated behavioral impairments induced by H2O2. Also, the latency of tail withdrawal increased significantly in the plant treated groups suggesting its analgesic effect. H2O2 induced a marked increase in liver biomarkers that was reversed in 250 mg/kg M. rotundifolia treated group. The obtained results suggested that M. rotundifolia had remarkable antioxidant and neuroprotective effects and may prevent oxidative stress related disorders.